A systems approach to the design of procedures necessary for the organisation of student training flights - College of Aeronautics, (Cranfield) (College of Aeronautics, 1964)
The project was designed to familiarise the group with the use of system design techniques. The objective was to synthesis a system which would be suitable for providing training flights for students at The College of Aeronautics, Cranfield.